The impact of adolescent achievement goal orientation on learning anxiety: The mediation effect of peer interaction - Kong, Haiyan; Wang, Guangfeng; Cheng, Dazhi; Li, Tian (Frontiers in Psychology, 2023)
Learning anxiety is one of the most important emotional disturbances, which also has a high incidence rate in adolescents. Peer interaction is critical and unique for adolescents. Although previous studies have found that achievement goal orientation has an important role in the development of learning anxiety, its mechanism has not been clarified. This study surveyed 470 adolescents (191middle school students and 279 high school students; 211 boys) and established a structural equation model to explore the mediating role of peer interaction in the influence of achievement goal orientation on learning anxiety. Results showed that (1) there were significant gender differences in mastery-avoidance goal orientation, peer interaction, and learning anxiety, and grade differences in performance-approach goal and performance-avoidance goal orientations; (2) mastery-approach, mastery-avoidance, and performance-avoidance goal orientations directly predicted learning anxiety; (3) and social anxiety in peer interactions had a mediating effect on the influence of mastery-approach, mastery-avoidance, and performance-avoidance goal orientations on learning anxiety. The findings extend theoretical considerations by teasing out the process of peer interaction affecting the relation between achievement goal orientation and learning anxiety. Additionally, the results have practical implications for the effective use of peer interaction to reduce learning anxiety.